2010
DOI: 10.1159/000286348
|View full text |Cite
|
Sign up to set email alerts
|

Depression as a Potential Explanation for Gender Differences in Health-Related Quality of Life among Patients on Maintenance Hemodialysis

Abstract: Background/Aims: The reasons for lower health-related quality of life (HRQOL) scores in women compared to men on maintenance hemodialysis (MHD) are unknown. We investigated whether depression accounts for gender differences in HRQOL. Methods: Cross-sectional study of 868 (40.9% women) Brazilian MHD patients (PROHEMO Study). We used the Kidney Disease Quality of Life Short Form to assess HRQOL and the Center for Epidemiological Studies Depression (CES-D) scale (scores from 0–60) to assess depression with scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 37 publications
4
43
0
4
Order By: Relevance
“…As the model included adjustment for patient's weight, these associations were independent of the gender and race weight differences. The association of race [27,28,29,30,31] and gender [32,33,34,35] with QOL in HD patients have long been noted. These may be secondary to spiritual beliefs [28], social factors [31,] psychological factors [29,34,35], how different genders or ethnic groups perceive their health level, or to different health expectations [30].…”
Section: Discussionmentioning
confidence: 99%
“…As the model included adjustment for patient's weight, these associations were independent of the gender and race weight differences. The association of race [27,28,29,30,31] and gender [32,33,34,35] with QOL in HD patients have long been noted. These may be secondary to spiritual beliefs [28], social factors [31,] psychological factors [29,34,35], how different genders or ethnic groups perceive their health level, or to different health expectations [30].…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, women are believed to have higher rates of depression and present for treatment more frequently [71]. This gender disparity in prevalence of depression was also evident in a sample of Brazilian hemodialysis patients, in which a greater percentage of women (51.8%) than men (38.2%) were found to meet criteria for depression (cutoff >18 on CES-D) [72]. Similarly, data from the Dialysis Outcomes and Practice Patterns Study (DOPPS), a large-scale, prospective, observational study of American and international hemodialysis patients, indicated that a higher percentage of the depressed patients were female [60].…”
Section: Prevalence Of Depressionmentioning
confidence: 91%
“…These differences may translate into systemic stress, increased risk and further poor compliance, all likely increasing death hazards. Supporting this, women undergoing hemodialysis have been reported to experience a higher prevalence of depressive symptoms and anxiety traits [101,102] .…”
Section: Gender Differences In Dialysis Therapy Adequacy and Patientmentioning
confidence: 96%